2021
DOI: 10.1016/j.resuscitation.2021.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Association between shockable rhythms and long-term outcome after pediatric out-of-hospital cardiac arrest in Rotterdam, the Netherlands: An 18-year observational study

Abstract: Introduction: Shockable rhythm following pediatric out-of-hospital cardiac arrest (pOHCA) is consistently associated with hospital and short-term survival. Little is known about the relationship between shockable rhythm and long-term outcomes (>1 year) after pOHCA. The aim was to investigate the association between first documented rhythm and long-term outcomes in a pOHCA cohort over 18 years.Methods: All children aged 1 dayÀ18 years who experienced non-traumatic pOHCA between 2002À2019 and were subsequently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…Mean age ranged from 1.5 to 6.4 years. Three studies were conducted in the United States of America [ 22 , 23 , 24 ], two were conducted in the Netherlands [ 25 , 26 ], one in Finland [ 27 ], and one in Taiwan [ 28 ]. Two studies were prospective cohort studies, and five were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mean age ranged from 1.5 to 6.4 years. Three studies were conducted in the United States of America [ 22 , 23 , 24 ], two were conducted in the Netherlands [ 25 , 26 ], one in Finland [ 27 ], and one in Taiwan [ 28 ]. Two studies were prospective cohort studies, and five were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of survival beyond 1 year, only two [ 25 , 26 ] studies reported this outcome. Albrecht et al reported a survival of 95% at a median follow-up time of 26.3 months, while Hunfeld et al reported a survival of 98% at a mean follow-up time of 24 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations